MANAGEMENT TRAINING IN THE SYSTEM OF FURTHER EDUCATION - G. G. Plotnikova (Образование и наука)
The research is aimed at curricula development in the system of further education based on the competence approach and integration of managerial training and practical applications. The study was carried out in accordance with the systematic approach considering the dynamics and interactions of structural elements of training system; and factorial approach identifying the optimization options of pedagogical process.The research methods include the theoretical analysis and synthesis, experimental data analysis, personal involvement method, and interviews.The author identifies the factors hindering the process of further managerial training; emphasizes the need for personal and professional competences development; and describes the competence matrix method, designed for balancing the requirements for the leadership training and based on the European and National Qualifications Frameworks.The research outcomes can be used for coordinating the system of further managerial training with the labor market demands.